Creative industry districts: an analysis of dynamics, networks and implications on creative clusters in Shanghai - He, Jinliao (Springer International Publishing Imprint: Springer, 2014)
This book provides insight into creative industries and spaces in Shanghai, which is the fastest growing megacity in China and center of modern economic development on a global scale. Underpinned by new approaches from economic geography and urban studies, it deals with the new relations between the creative economy and urban environment in Shanghai. At the point of transition in economy and society, China is recently striving to transform its economy from “made in China” towards “created in China”. Since the late 1990s, there have been broad discussions concerning the rapid rise of the creative economy. Creative or cultural industry is seen as the new engine of the regional growth for both developed economies and emerging nations. Over the last decade, creative clusters have been rapidly emerging in particular locations in the central city of Shanghai. This spatial phenomenon is explained in the book through an analysis of dynamics, networks and implications
Description based upon print version of record